SGS-LTER historical LTER soil water-neutron probe field data from across the Central Plains Experimental Range, Nunn, Colorado, USA, ARS study number 10 - Lauenroth, William K. (Colorado State University. Libraries, 1981)
This data package was produced by researchers working on the Shortgrass Steppe Long Term Ecological Research (SGS-LTER) Project, administered at Colorado State University. Long-term datasets and background information (proposals, reports, photographs, etc.) on the SGS-LTER project are contained in a comprehensive project collection within the Repository (http://hdl.handle.net/10217/100254). The data table and associated metadata document, which is generated in Ecological Metadata Language, may be available through other repositories serving the ecological research community and represent components of the larger SGS-LTER project collection. Long-term (1985-1992) dynamics and spatial variations in soil water below the evaporative zone were evaluated for a shortgrass steppe with a low and variable precipitation regime. Each of sandy loam, clay loam, and two sandy clay loam sites compromised a toposequence with upland, midslope, and lowland positions. Soil water was monitored at 15cm intervals providing estimates covering 22.5 to 97.5 cm depths. Soil water throughout the profile was highest in the clay loam and lowest in the sandy loam. However, stored soil water did npt vary systematically among slope positions.
Natural Resource Ecology Laboratory (NREL)
Shortgrass Steppe-Long Term Ecological Research (SGS-LTER)
Keywords: soil moisture; soils; inorganic nutrients; neutron probe; grasslands